The wrongs in reporting human rights how the media covered the killing of activist Chad Booc and the new Bataan 5 - Dumalag, Gabryelle Torres 1999
The Philippines was pushed into its 'worst human rights crisis' in post-Marcos history during former President Duterte's administration. Waging a war on dissent, state critics have been subject to red-tagging and grave abuses which the media reports on. This thesis examined how online mainstream, state and alternative media outfits, reported on the contentious event that led to the killings of the 'New Bataan 5' which consists of Lumad teacher and activist Chad Booc. a fellow Lumad teacher. a health worker and two drivers. State sources alleged that their deaths were a result of an encounter between the military and the New People's Army (NPA) which families and supporters of the victims denied. This study is anchored on Shaw's (2012) "diagnostic style of reporting" as human rights journalism which critically reflects the experiences of the victims, challenges the status quo set by the powerful, describes the causes of violence, and takes a more proactive role in humanitarian intervention to prevent abuses and promote human rights. This research is further guided by Bednarek and Caple's (2017) conceptualization of news values which constructs the newsworthiness of an event. Using content analysis, online news stories from six mainstream media organizations ABS CBN News, News 5, GMA News, Rappler, state media Philippine News Agency, and alternative media Bulatlat. Among these media outlets, only Bulatlat fully subscribed to the diagnostic style of reporting, framed the event as a human rights violation and published in-depth articles.